The causal impact of body mass index on metabolic biomarkers and nonalcoholic fatty liver disease risk - Bo Wang; Yanjiang Yang; Zhaoqiang Yin; Wenwen Yang (Scientific Reports)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is a growing global health concern linked to obesity. Methods This study employed a Mendelian randomization approach to explore the causal influence of BMI on metabolic biomarkers and the subsequent risk of NAFLD. We analyzed data from multiple sources, including 249 metabolic traits, to establish direct and mediating relationships among BMI, metabolic factors, and NAFLD risk. Results Our findings revealed a significant positive correlation between BMI and NAFLD across various datasets. We identified 176 metabolites associated with BMI, of which 106 were also linked to NAFLD. Importantly, 86 metabolites were found to mediate the relationship between BMI and NAFLD risk. Specifically, elevated levels of branched-chain amino acids, triglycerides, and certain cholesterol esters were notably associated with increased NAFLD risk, whereas changes in free cholesterol and phospholipid levels also played critical roles. Conclusion This study highlights the complex interactions between BMI, metabolic biomarkers, and NAFLD risk. By elucidating these relationships, we highlight potential targets for interventions aimed at reducing NAFLD incidence in populations with elevated BMI, ultimately contributing to improved metabolic health.